The Effect of Credit Procedures, and Credit Interest Rates on the Decision to Take Credit at Commercial Banks in MSMEs in Bali - Sukarnasih, Desak Made; Bhegawati, Desak Ayu Sriary (Cattleya Darmaya Fortuna, 2024)
This study examines the impact of interest rates and credit procedures on MSMEs' decisions to take loans from commercial banks. Using regression analysis, the research tests hypotheses with a sample of 100 MSMEs in Bali, selected from a population of 15,332 MSMEs using the Slovin method. Data was collected through a survey of MSMEs that had applied for or considered commercial bank loans in 2023. Results show that credit procedures have a positive and significant influence on MSMEs' loan decisions, while interest rates do not significantly affect their choices. These findings indicate that MSMEs prioritize the efficiency and ease of credit processes over interest rate considerations. The study highlights the importance of streamlining credit procedures to enhance financing access for MSMEs and recommends further research into other factors that may influence MSMEs' credit decisions. This research contributes to understanding the dynamics of MSME financing in the context of Bali's economic landscape.